Analisis BCOR Mempengaruhi Adopsi Sistem Manajemen Pengetahuan (KMS) - Faradillah Faradillah (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2017)
Knowledge Management as an approach in Information System development is used to develop a Knowledge Management System as supporting technologies. Knowledge Management Systems can be defined by aligniment the Knowledge Management Process in organization. Knowledge Management System (KMS) at the present time has become an important requirement for the company. Knowledge Management System (KMS) assist companies to store the knowledge possessed by its employees to deal with employee turnover, provide a competitive advantage, and improve the effectiveness of the company's operations. However, when doing KMS implementation required a readiness and preparation for implementing of a new system does not become a futility. This research intends to identify factors of KMS adopting in private universities as part of a preparation before the implementation of KMS in it. In this study, the author takes a case study at the University XYZ in Palembang as a research media by using Benefit Cost Oppotuniy and Risk (BCOR) Analysis as a research method. at this stage of data processing, the Author uses Expert Choice Application as an aid in data processing using AHP stages in order to find the priority factor in adopting KMS in private university. The results showed that the priority factor that affects in adopting KMS at University XYZ in Palembang is the Optimization factor of opportunity criteria.